112k views
2 votes
Find the missing factor.3y^2-2y-5=(y+1)( ? )

User Djra
by
4.3k points

1 Answer

2 votes

Given the following function:


\text{ 3y}^2\text{ - 2y - 5 = (y + 1)(?)}

Let's determine the missing factor:


\text{ 3y}^2\text{ - 2y - 5 = (y + 1)(?)}
\text{ 3y}^2\text{ - 2y - 5 = (y + 1)(A + B)}

Where:


\text{ A = }(3y^2)/(y)\text{ = 3y}
\text{ -2y = By + }(1)A
\text{ -2y = By + }(1)\text{(3y)}
\text{ -2y = By + 3y}
\text{ -2y - 3y = By}
\text{ -5y = By}
\text{ }\frac{\text{-5y}}{\text{ y}}\text{ = }\frac{\text{By}}{\text{ y}}
\text{ -5 = B}

Therefore, the missing factor will be:

(y + 1)(A + B) = (y + 1)(3y - 5)

The answer is 3y - 5

User ForguesR
by
4.6k points